Association of Disease Progression With Cardiovascular and Limb Outcomes in Patients With Peripheral Artery Disease: Insights From the EUCLID Trial. (October 2020) - Rymer, Jennifer A.; Mulder, Hillary; Narcisse, Dennis I.; Rockhold, Frank; Hiatt, William R.; Fowkes, F. Gerry; Baumgartner, Iris; Berger, Jeffrey S.; Katona, Brian G.; Mahaffey, Kenneth; Norgren, Lars; Blomster, Juuso I.; et al.
Abstract : Background: Patients with peripheral artery disease have a high risk of future cardiovascular disease events and mortality. Little is known about the changes in symptom classification over time in patients with peripheral artery disease and the association of changes in symptom classification with subsequent cardiovascular disease events. Methods: In this analysis of the EUCLID trial (Examining Use of Ticagrelor in Peripheral Artery Disease), we examined the changes in Rutherford classification (RC) of patients over 12 months. We examined the baseline characteristics of patients by change in symptom classification at 12 months (improved=decreased RC, no change, or worsened=increased RC), and the association between changes in symptom classification (RC) at 12 months and subsequent cardiovascular disease events. Results: Among 12 759 patients, 3240 (25%) were classified as improved by RC at 12 months, 8132 (64%) as no change, and 1387 (11%) as worsened. At 12 months, many patients who were asymptomatic or had mild/moderate claudication at enrollment had no change in symptom classification over 12 months (73.7% and 70.9%). Patients who worsened over 12 months were more likely to have comorbidities (diabetes mellitus and prior myocardial infarction) and more events (myocardial infarction, amputation, and major bleeding) by 12 months postrandomization, all P <0.001. Worsened symptom classification over 12 months was associated with increased risk of all-cause death (adjusted hazard ratio, 1.29 [95% CI, 1.03–1.62]), major amputation (adjusted hazard ratio, 4.12 [95% CI, 2.46–6.88]), and a composite of cardiovascular death, myocardial infarction, or stroke (adjusted hazard ratio, 1.30 [95% CI, 1.05–1.62]), all P <0.05 after 12 months postrandomization. Conclusions: Patients with comorbidities and prior history of cardiovascular disease events at baseline and within the first 12 months of the trial were more likely to have worsened symptom classification at 12 months. Worsening symptom classification over 12 months was associated subsequently with an increased risk of all-cause death, amputation, and a composite of cardiovascular death, myocardial infarction, or stroke. Abstract : Supplemental Digital Content is available in the text.